2009
DOI: 10.1002/jcp.21896
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus productively infects adrenocortical cells and induces an early cortisol response

Abstract: Following our recent findings on the presence of human cytomegalovirus (HCMV) in the normal human adrenal cortex and in adrenocortical tumors, especially in cortisol-secreting tumors, aim of the present study was to investigate the direct effects of HCMV infection on human adrenocortical cells. To this aim, both clinical isolates and laboratory strains of HCMV were used to assess the early effects of infection on human adrenocortical cell morphology, proliferation, gene expression, and steroidogenic function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…At present, the best characterized factors are by far the genetic ones, with specific alleles of the HLA complex conferring the highest risk (Erichsen et al, 2009b). Little is known about environmental factors, although the adrenal cortex has been described to be permissive to several viral, fungal and bacterial agents (Kelestimur, 2004;McLeod et al, 2011;Trevisan et al, 2009). Regarding endogenous factors, it has become increasingly recognized that adrenocortical cells have a wide range of immunological mediators in their repertoire, including HLA class II, TLRs, cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 98%
“…At present, the best characterized factors are by far the genetic ones, with specific alleles of the HLA complex conferring the highest risk (Erichsen et al, 2009b). Little is known about environmental factors, although the adrenal cortex has been described to be permissive to several viral, fungal and bacterial agents (Kelestimur, 2004;McLeod et al, 2011;Trevisan et al, 2009). Regarding endogenous factors, it has become increasingly recognized that adrenocortical cells have a wide range of immunological mediators in their repertoire, including HLA class II, TLRs, cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the immunosuppressive hormone cortisol inhibits TA in CD4 and CD8 T cells (Choi et al, 2008), whereas its analogue hydrocortisone promotes viral replication in latently infected cells (Lathey and Spector, 1991). Significantly, research has shown that CMV can directly increase cortisol production by its ability to infect and replicate in human adrenocortical cells, where it causes steroidogenesis (Trevisan et al, 2009). In conjunction, this group has previously reported an aberrant cortisol release in healthy CMV-positive individuals involving a flattened circadian decline (Steptoe et al, 2009), which implies a more constant level of exposure to the hormone.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that several pathogens (hepatitis B virus, cytomegalovirus, and HIV) may affect cortisol balance [3][4][5]. Zika virus (ZIKV)-induced pathology in symptomatic human neonates comprises small-for-gestational-age phenotype, lesions in the brain, microcephaly, epilepsy, and altered behavior associated with irritability, impatient crying, and anxiety [6].…”
mentioning
confidence: 99%